Засади фінансового забезпечення екологічної безпеки регіону - Колмакова, В.М. (Економіка природокористування і охорони довкілля, 2013)
У статті за результатами аналітичної оцінки виявлено актуальні екологічні проблеми Автономної Республіки Крим та запропоновано теоретико-методологічні підходи до вдосконалення фінансового забезпечення регіональної екологічної політики, що сприятиме підвищенню ефективності використання фінансових ресурсів та покращенню екологічної ситуації в регіоні. In this paper the results of analytical evaluation revealed the urgent environmental problems of ARC and suggests theoretical and methodological approaches to improve financial support for regional environmental policies that will increase the effectiveness of financial resources and the improvement of ecological situation in the region. A special place is also given to the development of organizational and economic mechanism of strategic management of environmental safety by creating special regional extrabudgetary funded emergency fund for the prevention and elimination of emergency situations Crimea. Thus the main source of the funds in the savings proposed emergency fund for the prevention and elimination of emergency situations in the Crimea, above all, can be a means of insurance potentially dangerous objects, penalties, charitable contributions, etc.